Urban Design Futures - Moor, Malcolm; Rowland, Jon (Taylor & Francis, 2006)
The last decade has seen the rise of urban design which has taken a central position in the new agendas for urban regeneration and renaissance. Urban design has moved from marginality to mainstream. The principles espoused by urban designers over the past thirty years are now accepted as key to a better urban environment and as we move towards greater sustainability, different ideas are emerging that are challenging some of the accepted urban design norms; urban design is at a watershed. Urban Design Futures presents essays from an international cast of authors to review progress and explore emerging ideas: should urban design reflect the future rather than recreate the past? What are the new driving forces that will shape urban living and hence urban design in the future? This book explores new concepts and points the way towards a series of urban design paradigms for the twenty-first century.